An Ultrathin Wideband Microwave Metamaterial Absorber Based on Frequency Selective Surface. (28th December 2021) - Han, Xuefeng; Wang, Yonghua; Xu, Jinkai; Yu, Huadong
Abstract: This article introduces a frequency‐selective surface‐based metamaterial absorber with small thickness and large bandwidth. The structure having an overall thickness of only 2 mm is manufactured on an FR4 substrate, and the size of the repeating unit is 10 mm × 10 mm. When electromagnetic waves incident perpendicularly on the absorber, it has an absorption bandwidth of 8.64 GHz (from 9.16 to 17.8 GHz),  covering most of the X‐band and Ku‐band. Results show that the lowest absorption rate reaches 91.5% while the highest is 99.85%, and the full width half maxima (FWHM) bandwidth is 10.5 GHz (from 8.8 to19.3 GHz). Thanks to extensive simulations, the structure is optimized. Furthermore, the electromagnetic parameters εeff and μeff images are drawn to illustrate the absorption mechanism, and the current images of the top and bottom layers are drawn to further support absorption mechanism. Finally, experiments are conducted to verify the absorption capacity of the structure as electromagnetic waves incident perpendicularly. Abstract : A metamaterial absorber based on a frequency‐selective surface is introduced. The material has a thickness of 2 mm and achieves a large absorption bandwidth without using resistive materials. The metamaterial absorber is fabricated using printed circuit board technology. The metamaterial absorber has the advantages of simple structure, low cost, light weight, etc.